Sara Arnold: capstone - Arnold, Sara, artist (Colorado State University. Libraries, 2022)
The artist's statement: My work addresses the nature of internet language and how it is comprehended in contemporary issues of self image. My interest is in a new era of “wokeness” that manifests through competition. My work tries to visually explain this phenomenon by addressing being chronically online. I want to express the moment of distortion that happens when information is regurgitated through a lens clouded by the need to be socially conscious in an altruistic fashion. The moment of distortion is described through real time video processing, the viewer of the work therefore becomes part of the art object as they are forced to see a distorted version of their person. The separation from the real world or analog world is defined by the output to the real time video processing; I want the viewer to see themselves become distorted, to reveal the unsee-able phenomenon that I'm describing. The use of text in my work is meant to emulate the impermanence of a social media timeline, as well as frequent subjects of internet discourse. This brevity is further stressed by a scrolling of the text as a motif in a few of my works. The use of text in my work is about examining how language is changed in internet spaces with the removal of aural conversation, and the addition of a slang - based vernacular. Language In Cyberspace focuses on the language used by Generation Z and Millennials on social media platforms. As a generation I find the language that is often used to talk about complex subjects such as socio-political movements, human rights, oppression of marginalized groups, and the power struggle of generations older, is often more casual and even uses memes or internet trends. The use of this more casual language often contradicts the subject matter of the text. In this piece I re-contextualize these texts using a familiar text to speech voice used heavily in memes to drown out the seriousness of the messages while also making content with darker themes more palatable. This piece considers the human side of internet language, as a coping mechanism. Expanding on media language as represented through text, audio, and visuals, Means of Communication uses internet language to inform different modes of communication, which is then manipulated to emphasize the ways information is distorted through exchange. Textual visuals, audio visualization, and the audio used in the piece are all informed by one another, each representing how communication of information through internet language is used differently. Additionally the different manipulations of the same piece of information echoes how thoughts and remarks of internet language are layered and informed by one another, and distorted by one another. The concept of the piece is based around the dematerialization of communication, exploring different representations of communication through sound, text, and the visualization of sound. The piece also acts as a sequel to "Language in Cyberspace”, however in this piece the means of communication "and visual representation of internet language informs the process of the piece.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art